Establishment Of Tissue Culture And Evaluation Of Biological Activities Of Jarum Tujuh Bilah (Pereskia Bleo Kunth) - Jaafar Sidik, Norrizah (2008)

(untitled)
Pereskia bleo is a leafy cactus which belongs to Cactaceae family and it is commonly used among the traditional medicine practitioners to prevent or treat cancer by consuming the leaves. As there is lack of information available on this plant, this research was carried out to determine the biological activities in natural plants and tissue culture materials. In order to produce standardize plant material for secondary metabolite production, tissue culture systems for Pereskia bleo was initiated and established. In vitro plantlets and tissues of Pereskia bleo were micropropagated in order to provide enough uniform explants for further tissue culture work and for extraction. The highest number of sterile explants (65.6%) was observed using fungicide for 20 minutes followed by 20% Chlorox® for 10 minutes. The growth characteristics on different types of basal media containing plant growth regulators were analyzed for maximum production of biomass: plantlets, calli and cell suspension. The highest number of multiple shoots (5.3 ± 0.5) was formed in MS basal medium supplemented with 2.22 μM BAP using shoot tips explants. Using node explants cultured onto MS supplemented with 8.88 μM BAP gave the highest number of multiple shoots (6.7 ± 0.58). Cell suspension growth was highest in MS basal media supplemented with 2.26 μM 2,4-D. Hairy root experiments revealed that both leaf and stem explants of Pereskia bleo were susceptible to all Agrobacterium rhizogenes (TR 105, LBA 9402, 8196, ATCC 15834) tested. Addition of acetosringone in the Agrobacterium rhizogenes culture increased the transformation frequencies of hairy root in Pereskia bleo. Results from brine shrimp lethality test showed no toxicity of the Pereskia bleo extracts occurred. The petroleum ether, chloroform and methanol leaf extracts showed strong in vitro antiproliferative activities (IC50 : 6.5 - 25.4 μg/ml) for MCF-7 (human hormone-dependent breast cancer cell line) and (IC50 : 19.3 - 26.8 μg/ml) for MDA-MB-231 (human hormone non-dependent breast cancer cell line). The IC50 value against HL-60 (human leukemia cell line) between 6.91 and 9.98 μg/ml for chloroform, petroleum ether and methanol extracts. Non-cytotoxic activity towards the non-tumour 3T3 mouse fibroblast indicated that the extracts exhibited selective mode of inhibition between tumor and non-tumor cells. The findings of antioxidative and antiproliferative activities of the plant extracts in vitro suggested that this species does contain antioxidant and cytotoxic compounds. The results obtained support the use of this species in traditional medicine for the prevention and treatment of cancer.